The Effect of Zeolite Addition in Growing Media on The Growth and Yield of Green Mustard (Brassica Juncea L.) - Azzahra, Annisa Ayu; Asnur, Paranita; Istiqlal, Muhammad Ridha Alfarabi; Malasari, Silvina (Jurnal Biologi Tropis, 2024)
Zeolite is a mineral widely used in agriculture due to its properties as an adsorbent, molecular sieve, and ion exchanger, as well as its high cation exchange capacity and selectivity. This study aims to analyze the effects of different zeolite application levels in the growing medium on the growth and yield of green mustard (Brassica juncea L.). The research was conducted in the smart agricultural sector of Gunadarma University Technopark from March to June 2024. A Randomized Complete Block Design (RCBD) with a non-factorial approach was employed, utilizing a single indicator plant—green mustard. The planting media consisted of soil, chicken manure, and cocopeat in a 1:1:1 ratio as the control. Zeolite was incorporated at three different levels: 40%, 45%, and 50%. Each treatment included ten repetitions with six samples, resulting in a total of 240 experimental units. The findings indicate that the optimal zeolite application level for green mustard growth is 45%, producing a plant yield of 17.75 tons per hectare. This represents a 5% improvement in efficiency compared to previous studies, which suggested that 50% zeolite was optimal. Additionally, the 45% zeolite treatment demonstrated a significant yield increase compared to the control treatment, which produced only 8.32 tons per hectare. These results highlight the potential of zeolite to enhance soil fertility and improve crop productivity.